Norman Theory and the Formation of Russian Statehood - Dmitriy I. Satushev; Dmitriy D. Ryumin; Ilya A. Sarankin (RUDN Journal of Public Administration, 2023)
The authors analyze the question of the origin of Russian statehood in ancient times. The main goal of the research is to study economic and social state of Russia at the beginning of the VIth century. The authors conduct a detailed analysis of the Norman and anti-Norman theories. They conclude assessment of the degree of influence of each of the theories on the formation of Russia as a full-fledged state.